Sonography : principles and instruments - Kremkau, Frederick W. (St. Louis, Missouri : Elsevier, 2021)
This book is intended for sonography students, allied-health personnel, and physicians who seek an understanding of the principles and instruments of diagnostic sonography. The purpose of this book is to explain how contemporary diagnostic sonography works. It serves as a textbook on sonographic principles in educational programs and helps readers to scan safely and effectively, to handle artifacts skillfully, and to prepare for registry and board examinations. The content of the book is driven by the author's assessment of contemporary technology in the field and his 50-year experience in teaching this material in the medical school environment and at conferences and seminars. Although this latest edition includes newer developments in the field, the emphasis is on the fundamentals. Important note for readers, instructors, and students: This 10th edition of the textbook introduces a significant change in the approach to understanding and applying the principles of sonography - namely, that there are now two underlying principles of operation extant in the variety of sonographic systems that are commercially available. This requires a profound change in how we approach learning about these systems, that is, there is not just one principle of operation as there has been for 50 years, but rather two, with implications for how they are managed throughout this textbook. There are significant differences between the two, not only in the underlying principle of operation, but in the implications for various characteristics and features of these systems. Therefore in this book a parallel approach is necessitated to illuminate these differences. This will be necessary as long as there are two operating principles, a period of years the length of which no one knows. As long as we are sending ultrasound into the body and receiving ultrasonic echoes, there will be sonographic systems. But what we do with the returning echoes will be radically different depending on the processing principles applied. This new edition has expanded the number of chapters dedicated to Principle 2 and has new illustrations and images demonstrating the latest and best images from the newest equipment as well as expanded content on volume imaging, elastography, and sophisticated echo acquisition techniques, keeping students up to date with the latest technology.
1. Sonography -- A window into the human body -- 2. Ultrasound: Sound we don't hear -- 3. Transducers: Sending and receiving -- 4. Instruments: Imaging anatomy with Principle 1 -- 5. Instruments: Imaging motion and flow with Principle 1 -- 6. Instruments: Imaging anatomy, motion, and flow with Principle 2 -- 7. Artifacts: What can go wrong -- 8. Is it performing well? -- 9. Is it safe? -- 10. To conclude -- Appendix A. Lists of symbols -- Appendix B. Compilation of equations -- Appendix C. Mathematics review.
Includes bibliographical references and index.
Keywords: Ultrasonography